'A horror movie with a happy ending': childbirth from the father's perspective. Issue 3 (17th November 2020) - Herrera, Florencia
ABSTRACT: This article analyzes how men in Chile narrate the birth of their first child in order to understand how they elaborate their masculine identity in the feminized field of reproduction. It seeks to make a contribution to masculinity studies by (a) describing the position that men have in childbirth and (b) applying the concept of hegemonic masculinity to the context of reproduction. We conducted in-depth interviews with 22 first-time fathers, before and after the baby's arrival. Our findings show how interviewees feared falling short of gendered expectations. During labor, they hoped to protect the woman but later realized they had no control. In their accounts of the birth, the men: (a) incorporate elements of hegemonic masculinity in order to present a more respectable masculine identity and (b) incorporate elements associated with the feminine in order to put themselves in a more central position in relation to the baby. For these fathers, hegemonic masculinity is valid as an ideal with which they seek to align themselves so as to give legitimacy to their position in the reproductive context. There are, however, signs that this ideal is changing so that a deep early bond with the newborn child becomes 'the manly thing to do.'